Lightweight SDN/NFV-based framework for dynamic data-flow and network slice adaptation - Sumbal Zahoor; Ali Mamoon (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2026)
The increasing demand for responsive and reliable network services in next-generation communication systems has intensified the need for dynamic resource management and quality of service (QoS) assurance. Software-defined networking (SDN) and network function virtualization (NFV) provide programmability and flexibility for modern networks. However, practical platforms that demonstrate real-time adaptive behavior remain limited. This study differs from prior simulation-focused work by demonstrating real-time adaptive slice control in a reproducible container-based SDN/NFV emulation environment. A bottleneck-aware slice controller is developed to classify degradations as network-limited, server-limited, or service failure using joint indicators, and to select rerouting or service migration using stability constraints and a lightweight action-cost model. Experimental results show that throughput is restored to above 90% of nominal capacity. Recovery typically occurs within two to three control iterations. Service continuity is maintained with low control-plane overhead. The work provides a reproducible experimental baseline and a decision mechanism that reduces incorrect reroutes/migrations under ambiguous key performance indicator (KPI) drops.